Generasi Muda Peduli: Kontribusi Nyata untuk Lingkungan Bersih dan Sehat - Jannati Tangngisalu; Muh. Akob Kadir; Ishak Ishak; Jamilah Saleh; Sahidah Sahidah; Marwah Yusuf; Abd Rajab; Hasyim Mochtar (Lembaga Pengembangan Kinerja Dosen, 2025)
This community service activity aims to increase awareness of the younger generation in Sanrobone Village, Takalar in maintaining environmental cleanliness and health through an educational and participatory approach. Activities include counseling on 3R waste management (Reduce, Reuse, Recycle), composting training, the formation of a village waste bank, and real actions in the form of planting trees and cleaning water channels. The results of the activity showed a significant increase in the understanding and skills of young people in managing waste and protecting the environment. In addition, the formation of the Sanrobone Village Waste Bank is the first step in efforts to reduce plastic waste and increase the economic value of inorganic waste. This activity has succeeded in fostering the commitment of the younger generation as pioneers of a sustainable clean and healthy environment movement in the village.